Pengimplementasian Tingkat Ketepatan Waktu Kelulusan Siswa (Studi Kasus Di MTS Nur Ibarhimy) Menggunakan Algoritma C4.5 - Amansyah, Rizky; Masrizal, Masrizal; Munthe, Ibnu Rasyid (Jurnal Informatika, 2024)
Education has a very important role in shaping the individual and directing the development of society. As an educational institution, MTS Nur Ibrahimy has a responsibility to improve the quality and efficiency in the implementation of Education. MTS Nur Ibrahimy is located in Rantauprapat, Rantau Selatan district, Labuhanbatu Regency. MTs Nur Ibrahimy has been established since 2000 and has produced a number of students who successfully completed their education at this school. Along with technological advances, pattern exploration can be done by using data classification techniques obtained through the data mining process. Data mining is generally done because of the large amount of data, which can be used to generate patterns and useful knowledge in the business operations of a company. One of the methods developed in data mining is a way to dig up existing data to build a model, and then use the model to recognize other data patterns that are not contained in the stored database. In this context, a classification model is created to identify data patterns related to "Passed" or "not passed" status classes, based on pattern Determination results from training data. The Decision Trees Model is an implementation of the classification model in data mining. This Model builds a decision tree from training data consisting of records in a database. The C4.5 algorithm is one of the data classification algorithms that uses decision tree techniques and is able to manage numerical (continuous) and discrete data, and can handle missing attribute values. This algorithm produces rules that are easy to interpret. C4.5 has been tested in various classification cases, including in medical, trade, personnel, and various other fields.